MEDIA VLOG SEBAGAI STRATEGI KOMUNIKASI DALAM METODE PEMBELAJARAN DI KALANGAN SISWA DALAM MENGHADAPI PADEMIC COVID 19 - Amalliah Amalliah; Ria Yunita (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Vlog as an audio visual media becomes one of the communication strategy choices in the learning and teaching process in the middle of the covid 19 virus pandemic that is plaguing the world. Work, worship and learning activities and activities are carried out at home to prevent the spread of the covid virus 19. Learning at home does not reduce creativity, enthusiasm of students to keep learning because it can be data using online media, Project Based Learning is a method of learning with vlog media where students are creative in completing assignments at home and this can also reduce the sense of boredom staying at home other than through vlog tutorial subjects become interesting so that students are very easy to understand.